До питання дослідження садиби гетьмана Кирила Розумовського в Батурині на вулиці Київській (на матеріалах ЦДІАК України, м. Київ) - Фурсова, Ю. (Сiверянський лiтопис, 2019)
У статті на основі нововиявленого документу з ЦДІАК України в м. Києві досліджено та проаналізовано споруди, що входили до складу садиби гетьмана Кирила
Розумовського в Батурині. Подані у статті матеріали дають змогу конкретніше
дізнатися про забудову Батурина в часи життя та гетьманування Кирила Розумовського та в подальшому здійснити наукову реконструкцію його гетьманської садиби. The question of the construction of Baturin in the times of Hetman Kirill Razumovsky
and his hetman’s house on Kievskaya street remains today insufficiently studied, despite the
various scientific studies available. In the article on the basis of what kind of document with
the CDCS of Ukraine, the city of Kiev has been investigated and analyzed structures that
were part of the estate of Hetman Kyrylo Rozumovsky in Baturyn, which was located on the
Kyivska street (modern address Yushchenko Street 47).
The study of this document is important for scientific research, because it contains a
detailed description of each structure and to some extent describes interior decoration of
buildings.
The analysis of the document shows that a significant part of the manor was occupied
by the main house with outbuildings. In addition, the estate included service buildings: a residence
for musicians and an architect who were located on the service of the hetman, kitchen,
wardrobe, carriage and stables, barns. For confirmation of the idea that this is exactly the
hetman’s manor, the article cites comparison with the document «Inventory of Baturynska
and Ropska, his lordship of the prince Andrei Kirilovich Rozumovsky volosts consisting of
Chernihiv Provinces in Konotop and Novozybkiv counties. Started September 1836 on 26-th
day. Analysis and comparison of these documents give reason to argue that we are talking
about the estate of the hetman on the Kyivska street. The materials indicated in the article
cannot provide a complete picture of estate of Hetman Kyrylo Rozumovsky, therefore need
further scientific research.